Small bowel exploration and resection using single‐port surgery: a safe and feasible approach. (20th December 2012) - Dhumane, P.; Mutter, D.; D'Agostino, J.; Mavrogenis, G.; Leroy, J.; Marescaux, J.
Abstract Aim The aim of this study is to demonstrate the efficacy of wireless capsule endoscopy for preoperative identification of bleeding sources and/or small bowel tumours in surgical patients and to evaluate the feasibility of single‐port surgery in the treatment of such pathologies. Method Five patients presenting with obscure gastrointestinal bleeding or/and mild small bowel obstruction were investigated to diagnose and localize the bleeding source or tumour using capsule endoscopy imaging, and, if necessary, with other investigative modalities. All patients were operated on using single‐port surgery for small bowel exploration, lesion confirmation, small bowel resection and anastomosis. Results Small bowel pathology was successfully detected by video capsule endoscopy in three of four patients, and was further substantiated by contrast CT, double‐balloon endoscopy or enteroclysis. Complete small bowel exploration, intra‐operative identification and oncological resection of the involved segment and anastomosis (intracorporeal and extracorporeal) was successfully performed in all five patients using single‐port access without any complication, morbidity or mortality. Conclusion This study demonstrates the feasibility and safety of single‐port small bowel resection performed after a high‐quality preoperative localization of the tumour.